Medicaid and the Cost of Improving Access to Nursing Home Care - Gertler, Paul J. (The Review of Economics and Statistics, 1992)
In this paper I show that the Medicaid program can improve the access of financially indigent patients to nursing home care by raising the rate of return paid on Medicaid patients' care, but only at the cost of lower quality of care. To quantify the policy tradeoff, I derive expressions for the elasticity of access with respect to total Medicaid expenditures and the elasticity of access with respect to quality. These elasticities expressions are complicated by the fact that Medicaid payment formulas are cost based and, therefore, depend on the quality choices of nursing homes. Using New York State data, I find that a 10% increase in Medicaid expenditures induces a 4.1% increase in Medicaid patient care but also reduces nursing home expenditures on patient services by about 3.4%.